Reality Group Counseling to Increase Emotional Intelligence and Happiness (Jurnal Bimbingan Konseling, 2019)
This research was design to examine and analyze the effectiveness of reality group counseling to increase emotional intelligence and happiness of students. This study used a pre-test – post-test control group design. The purposive sampling technique was used to select 14 students as experimental subjects placed randomly into two groups so that each group consisted of seven students. The MANOVA test results showed that reality group counseling is effective in increasing emotional intelligence (F(3.10) = 106.453; ηp2 = 0.939; p < 0.01) and happiness (F(3.10) = 261.248; ηp2 = 0.969; p < 0.01). Furthermore, the Paired Sample t-test results showed that in the experimental group there was an increase in emotional intelligence (t = t(3.10) = 16.051; p < 0.01) and happiness t(3.10) = 29.289, p < 0.01) The control group showed no significant increase in the level of emotional intelligence t(3.10) = 2.750, p > 0.05) and happiness t(3.10) = 2.066, p > 0.05). The findings of this study conveyed that the reality group counseling is effective in increasing emotional intelligence and happiness.